AD reception research: Some methodological considerations - Chmiel, Agnieszka; Mazur, Iwona (EUT, 2012)
AD reception research, or collection of feedback from the blind and partially sighted as the target audience of audio described films, seems to be one of the best sources of information to be applied when creating both AD standards and audio descriptions proper. This paper presents experiences gained by the authors when conducting two reception studies. The first one involved a questionnaire distributed to 18 viewers with vision dysfunctions immediately after two screenings of audio described films. The other one is a larger-scale work-in-progress, whose results will be applied in the development of Polish AD standards reflecting the preferences of the blind and visually impaired viewers in Poland, where the participants are being interviewed and presented with AD samples. The authors discuss various methodological issues, including problems with obtaining a sufficient number of participants, reflecting feedback from visually- impaired AD consultants in the surveys and discovering user preferences. It is suggested that responses concerning objectivity or subjectivity of descriptions should be elicited indirectly (implicitly) rather than directly (explicitly) and that research results are more meaningful if interviews involve comprehension questions and AD samples.
Keywords: audio description; reception research; AD standards